Investigating the impact of Precision Teaching on aspects of motivation towards literacy learning for male pupils in Year 5 and Year 6 - Critchley, Anna (2014)
This thesis project was designed to review the impact of Precision Teaching on elements of motivation and self-efficacy of male pupils in Year 5 and Year 6. Precision Teaching (PT) is a formative assessment based intervention, incorporating the principles of the learning hierarchy (Haring, Lovitt, Eaton, & Hansen, 1978), to deliver individually tailored teaching supported by continuous assessment and feedback. A mixed methods design incorporated single case experimental designs and qualitative interviews with the purpose of exploring the impact of PT on attribution style, locus of control and self-efficacy of pupils. Data was gathered using an adaption of the Multi-dimensional Measure of Children’s Perceptions of Control (Connell, 1985), Myself as a Learner (Burden, 1999) and structured interviews with participants. Staff at three schools implemented Precision Teaching with participants following training in this intervention. Results indicate no significant direction of change for internal, powerful others or unknown control over learning for pupils completing PT sessions, with all pupils displaying high internal causal attributions for their learning outcomes. Wider variation in unknown and powerful others control responses during intervention phases indicates that some change may have occurred in pupil perceptions of these elements. Of the four cases described, evidence of increased self-efficacy was found in one case. Analysis of interview data suggested that mechanisms of challenge, feedback of learning changes, and increased competence were potential mechanisms of motivation change initiated by PT. The paper concludes that further research is required to explore these mechanisms with a wider range of participants, and the impact of PT through closer analysis of participant attributions and loci of control over learning outcomes.